Prognostic Significance of Pretreatment Neutrophil-to-Lymphocyte Ratio, Platelet−to−Lymphocyte Ratio, or Monocyte-to-Lymphocyte Ratio in Endometrial Neoplasms: A Systematic Review and Meta−analysis - Leng, Jiali; Wu, Fei; Zhang, Lihui (Frontiers in Oncology, 2022)
Aim: NLR, PLR, or MLR has been shown to be related to the poor prognosis of cervical cancer, ovarian cancer, and other malignant tumors, but their role in predicting the prognosis of endometrial cancer is still controversial. Therefore, we conducted this meta-analysis to more accurately evaluate the effectiveness of NLR, PLR, or MLR in predicting the prognosis of EC. Methods: This review systematically searched for relevant publications in databases of the Cochrane Library, PubMed, EMBASE, CNKI, WanFang, VIP, and CBM database. Pooled hazard ratios (HR) with 95% confidence intervals (95% CI) were determined and used to explore the association between inflammatory biomarkers and overall survival (OS), progression-free survival (PFS) and disease-free survival (DFS) in a random-effects model. We also conducted subgroup analysis and publication bias in this meta-analysis. Stata 12.0 was used for statistical analysis. Results: This meta-analysis contained 14 eligible studies. Our results showed NLR or PLR was associated with OS (NLR: HR 2.51, 95% CI 1.70-3.71, p<0.001 in univariate analysis [Ua]; HR 1.87, 95%CI 1.34-2.60, p<0.001 in multivariate analysis [Ma]. PLR: HR 2.50, 95%CI 1.82-3.43, p<0.001 in Ua; HR 1.86, 95%CI 1.22-2.83, p=0.004 in Ma), but MLR was not associated with OS (HR 1.44, 95%CI 0.70-2.95, p=0.325 in Ua; HR 1.01, 95%CI 0.39-2.60, p=0.987 in Ma). Further subgroup analysis found that the correlations were not affected by race, cut-off value, sample size or treatment. Our meta-analysis showed that NLR or PLR was associated with DFS (NLR: HR 2.50, 95% CI 1.38-4.56, p=0.003 in Ua; HR 2.06, 95%CI 1.26-3.37, P=0.004 in Ma; PLR: HR 1.91, 95% CI 1.30-2.81, p=0.001 in Ua). And NLR was associated with PFS only in Ua (HR 1.71, 95% CI 1.04-2.81, p=0.035 in Ua; HR 1.79, 95%CI 0.65-4.89, P=0.257 in Ma). But MLR was not associated with DFS (HR 0.36, 95% CI 0.03-4.13, p=0.409 in Ua). Conclusions: Our results indicated pretreatment NLR and PLR were biomarkers of poor prognosis in patients with endometrial cancer. The results indicated that NLR or PLR was associated with OS and DFS, and NLR was associated with PFS only in Ua. But MLR was not associated with OS or DFS.